2014
DOI: 10.1128/jvi.02281-13
|View full text |Cite
|
Sign up to set email alerts
|

The ha72 Core Gene of Baculovirus Is Essential for Budded Virus Production and Occlusion-Derived Virus Embedding, and Amino Acid K22 Plays an Important Role in Its Function

Abstract: b ha72 of Helicoverpa armigera nucleopolyhedrovirus (a homologue of ac78) was identified as a conserved late baculovirus gene and characterized. HA72 localizes in the intranuclear ring zone. By generating mutants, we showed that HA72 is essential for budded virus (BD) production and occlusion-derived virus (ODV) embedding. HA72 also interacted with P33, a baculoviral sulfhydryl oxidase. A point mutation of amino acid 22 from lysine to glutamic acid curtailed BV production and precluded ODV occlusion as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…A recent study demonstrated that ac78 was required for nucleocapsid egress from the nucleus [ 12 ]. Many proteins are localized to the ring zone of infected nuclei, such as Ac76 [ 29 ], P33 [ 13 ], Ac93 [ 19 ], and E25 [ 30 ]. The ring zone is very important for nucleocapsid envelopment and egress from the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that ac78 was required for nucleocapsid egress from the nucleus [ 12 ]. Many proteins are localized to the ring zone of infected nuclei, such as Ac76 [ 29 ], P33 [ 13 ], Ac93 [ 19 ], and E25 [ 30 ]. The ring zone is very important for nucleocapsid envelopment and egress from the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…HA72 was demonstrated to be required for BV production and ODV embedding. Moreover, the IPLKL motif at the N terminus was shown to play an important role in its function [ 13 ]. More recently, Li et al found that Ac78 was not essential for BV production and ODV formation [ 11 ], which was a contradictory result.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear if abnormal nucleocapsids cannot be embedded because defective or missing structural proteins affect nucleocapsid morphology, are necessary to interact with other factors to mediate the embedding process, or provide nucleocapsid stability. Ac92 has been reported to interact with the human and insect p53 (Prikhod’ko et al, 1999; Wu et al, 2013) and HA72 (Ac78 ortholog), a Heliothis armiguera NPV factor (HearNPV) with a putative fumarate reductase flavoprotein motif (Huang et al, 2014). However, whether these interactions have functional significance has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of ha72 , the ac78 ortholog, and ac92 result in BV production and occlusion defects (Huang et al, 2014; Nie et al, 2011; Tao et al, 2013a; Wu and Passarelli, 2010). In addition, P33 (HearNPV Ac92 ortholog) and HA72 localize to the intranuclear ring zone of infected cells (Huang et al, 2014; Nie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation